Bicondylar Tibial Plateau Fractures: What Predicts Infection?. Issue 20 (15th October 2022) - Olszewski, Nathan; Manzano, Givenchy; Wilson, Eleanor; Joseph, Noah; Vallier, Heather; Pawlak, Amanda; Kottmeier, Stephen; Miller, Adam; Gary, Joshua; Namm, Joshua; Miller, Anna; Gupte, Guarang; et al.
Abstract : Objectives: The purpose of this study was to identify the patient, injury, and treatment factors associated with infection of bicondylar plateau fractures and to evaluate whether center variation exists. Design: Retrospective review. Setting: Eighteen academic trauma centers. Patients/participants: A total of 1, 287 patients with 1, 297 OTA type 41-C bicondylar tibia plateau fractures who underwent open reduction and internal fixation were included. Exclusion criteria were follow-up less than 120 days, insufficient documentation, and definitive treatment only with external fixation. Intervention: Open reduction and internal fixation. Main outcome measurements: Superficial and deep infection. Results: One hundred one patients (7.8%) developed an infection. In multivariate regression analysis, diabetes (DM) (OR [odds ratio] 3.24; P ≤ 0.001), alcohol abuse (EtOH) (OR 1.8; P = 0.040), dual plating (OR 1.8; P ≤ 0.001), and temporary external fixation (OR 2.07; P = 0.013) were associated with infection. In a risk-adjusted model, we found center variation in infection rates ( P = 0.030). Discussion: In a large series of patients undergoing open reduction and internal fixation of bicondylar plateau fractures, the infection rate was 7.8%. Infection was associated with DM, EtOH, combined dual plating, and temporary external fixation. Center expertise may also play a role because one center had a statistically lower rate and two trended toward higher rates after adjusting for confounders. Level of evidence: Level IV—Therapeutic retrospective cohort study.